Bio N Fertilization on Corn - Sumagaysay, Clemencia L (The International Journal of Biotechnology, 2014)
This study was conducted to evaluate the production of corn as affected by Bio – N inoculant with the different levels of fertilizers fertilization at Maglambing Tagbina, Surigao del Sur during wet/rainy season. Randomized Complete Block Design (RCBD) with five (5) treatments and three (3) replications was applied. The treatments were: T1 Bio – N inoculant, T2 Bio – N + Farmer’s Practice, T3 Bio N + ½ Recommended Rate (RR), T4 Bio N + Recommended Rate (RR) + Organic Fertilizer, T 5 Bio N + Recommended Rate (RR). Results showed that treatment 3 or the application of Bio –N combined with half of the recommended rate of fertilizers obtained a significant result in terms of ear length, ear weight and grain yield of corn. Treatment 3 Bio – N + ½ Recommended Rate of fertilizer recorded the most promising combination of fertilizer as it optimized corn production during wet/rainy season.